Gender analysis analysis of the strategies for poverty alleviation of men and women at the household level in Barangay Igdalaquit, Miag-ao - Castromayor, Mary Jane J.
This project aims to determine the different poverty alleviation initiatives that men and women do at the household level to address their poverty need and to determine how gender sensitive are the strategies undertaken by men and women at the household level to alleviate property using Longwe's Framewrok of Analysis. The respondents of the study were 40 households' residents (N=40) of Barangay Igdalaquit, Miag-ao The researchers used purposive sampling procedures in selecting the specific barangay and the sample household respondents. The result of the study show that household's respondents undertake six different majors' poverty alleviation strategies namely: engagement in entrepreneurial activities, employment, credit, agricultural activities, budgeting and sending children to school. With the aid of Longwe Framework, the researcherrs determine perception of households respondents whether each povert alleviation strategies addresses male and female level of welfare, access, conscientization, participation and control over-decision making resources and benefits. There are six major poverty alleviation strategies at the household level identified by respondents' namely entrepreneurial activities, employment, credit, agricultural activities, budgeting and sending children to school. Poverty alleviation strategies which include entrepreneurial activities, credit budgeting and sending children to school are gender sensitive. The government officials both in barangay and municipal level should initiate specific actions to integrate women's concerns and priorities in the development policy and activity. The barangay should utilize the available gender budgets for trainings and workshop for men and women that will allow both genders to realize the great importance of women's participation in all kinds of househol, organization and community activities. There should be more related research studies that need to be conducted to determine how gender sensitive are the policies, rpograms and strategies formulated and implemented not only in the household level but taken into account the organization and community level.